Perchlorate, nitrate, and thiocyanate: Environmental relevant NIS-inhibitors pollutants and their impact on thyroid function and human health - Serrano-Nascimento, Caroline; Nunes, Maria Tereza (Frontiers in Endocrinology, 2022)
Thyroid disruptors are found in food, atmosphere, soil, and water. These contaminants interfere with the thyroid function through the impairment of thyroid hormone synthesis, plasma transport, peripheral metabolism, transport into the target cells, and thyroid hormone action. It is well known that iodide uptake mediated by the sodium-iodide symporter (NIS) is the first limiting step involved in thyroid hormones production. Therefore, it has been described that several thyroid disruptors interfere with the thyroid function through the regulation of NIS expression and/or activity. Perchlorate, nitrate, and thiocyanate competitively inhibit the NIS-mediated iodide uptake. These contaminants are mainly found in food, water and in the smoke of cigarettes. Although the impact of the human exposure to these anions is highly controversial, some studies indicated their deleterious effects in the thyroid function, especially in individuals living in iodine deficient areas. Considering the critical role of thyroid function and the production of thyroid hormones for growth, metabolism, and development, this review summarizes the impact of the exposure to these NIS-inhibitors on thyroid function and their consequences for human health.